The Promotion of Employment and Earning Opportunity of Women in Europe through Gender Mainstreaming. With Special Emphasis on Austria - Gudrun Biffl (Austrian Institute of Economic Research (WIFO), 2008)
The European Union has developed a complex strategy and policy coordination process to promote gender equality in all community policies through "gender mainstreaming". While every member country has to promote the policy objective of gender equality, the instruments implemented to that end may differ. Different institutional structures and gender roles in the society may result in different outcomes of the same policy measure. Therefore every country has to choose those instruments best fitted to achieve gender equality. This paper outlines the various positions of the individual member countries relative to gender relations, with a special emphasis on Austria. Overall, it is the state and public sector institutions which tend to take a lead in implementing affirmative action programmes, in the main positive discrimination of women (quota regulations, targets) and enforcement of antidiscrimination legislation. Affirmative action programmes in private industry are not a universal feature in all EU countries. While gender equality is pursued as a moral issue in its own right, it is also an instrument to combat the negative impact of ageing of the European populations on welfare budgets and economic growth.
Keywords: 330; Gender Mainstreaming; equal opportunity; gender gap; models of social organisation; outsourcing of household production; gender segregation; Gleichstellungspolitik; EU-Recht; Weibliche Arbeitskräfte; Lohnstruktur; Arbeitsmarktdiskriminierung; Familie-Beruf; Soziale Ungleichheit; Ehe; Österreich; EU-Staaten